Building of the criteria for determining of key marine areas of the Vietnam national plans for biodiversity conservation - Hung, Le Van; Hoe, Nguyen Dinh (Academia Journal of Biology, 2014)
In this paper, the construction method outlined criteria identify key sensitive areas (hot spots) of interest of marine ecosystems in the planning of Biodiversity Conservation in Vietnam. Set up criteria for determining the influence of the nature and impact of humans on the ecosystem of the national park of marine ecosystems was studied (ecosystem of mangroves, coral reefs, sea grass, upwelling ecosystems). The research methodology was based on: Rapid Assessment Method participatory (PRA); Inventory method matrix environment (Environmental Inventory) Dirk et al. and UNEP; Methods inherited, information collected through workshops, documentation gathering, investigation, networking internets. The results of this study have built the criteria for determining the sensitivity of concern identified through the index sensitivity to resource Biodiversity (Biodiversity Vulnerability Index-BVI) or the pressure of self- spiders and humans to biodiversity through the establishment of criteria, evaluation criteria and case studies. These are the initial results of the index determines the sensitivity index of BVIh to evaluate the effects of human impact and natural conditions in the forest ecosystem should be considered in Biodiversity Conservation Planning in our country.